Genomic landscape of retinoblastoma in Rb−/−p130−/− mice resembles human retinoblastoma. Issue 3 (21st November 2016) - Kooi, Irsan E.; van Mil, Saskia E.; MacPherson, David; Mol, Berber M.; Moll, Annette C.; Meijers‐Heijboer, Hanne; Kaspers, Gertjan J. L.; Cloos, Jacqueline; te Riele, Hein; Dorsman, Josephine C.
Abstract : Several murine retinoblastoma models have been generated by deleting the genes encoding for retinoblastoma susceptibility protein pRb and one of its family members p107 or p130. In Rb −/− p107 −/− retinoblastomas, somatic copy number alterations (SCNAs) like Mdm2 amplification or Cdkn2a deletion targeting the p53‐pathway occur, which is uncommon for human retinoblastoma. In our study, we determined SCNAs in retinoblastomas developing in Rb −/− p130 −/− mice and compared this to murine Rb −/− p107 −/− tumors and human tumors. Chimeric mice were made by injection of 129/Ola‐derived Rb −/− p130 −/− embryonic stem cells into wild type C57BL/6 blastocysts. SCNAs of retinoblastoma samples were determined by low‐coverage (∼0.5×) whole genome sequencing. In Rb −/− p130 −/− tumors, SCNAs included gain of chromosomes 1 (3/23 tumors), 8 (1/23 tumors), 10 (1/23 tumors), 11 (2/23 tumors), and 12 (4/23 tumors), which could be mapped to frequently altered chromosomes in human retinoblastomas. While the altered chromosomes in Rb −/− p130 −/− tumors were similar to those in Rb −/− p107 −/− tumors, the alteration frequencies were much lower in Rb −/− p130 −/− tumors. Most of the Rb −/− p130 −/− tumors (16/23 tumors, 70%) were devoid of SCNAs, in strong contrast to Rb −/− p107 −/− tumors, which were never (0/15 tumors) SCNA‐devoid. Similarly, to human retinoblastoma, increased age at diagnosis significantly correlated with increased SCNA frequencies. Additionally, focal loss of Cdh11 was observed in one Rb −/− p130 −/− tumor, which enforces studies in human retinoblastoma that identified CDH11 as a retinoblastoma suppressor. Moreover, based on a comparison of genes altered in human and murine retinoblastoma, we suggest exploring the role of HMGA1 and SRSF3 in retinoblastoma development. © 2016 Wiley Periodicals, Inc.